1986
DOI: 10.1161/01.str.17.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Community Hospital-based Stroke Programs: North Carolina, Oregon, and New York. I: Goals, objectives, and data collection procedures.

Abstract: SUMMARY In order to assess the impact of variations in stroke care on outcomes, and to make geographic comparisons, the three Community Hospital-Based Stroke Programs in North Carolina, Oregon, and New York, aggregated their data on 4,132 hospitalized stroke patients. Complete demographic data or "Major Profile" were obtained on 2,390 (57.8%) of the 4,132 stroke patients. This includes those patients on whom informed patient and physician consents were obtained during the hospitalization. Of the major profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
17
0
2

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 40 publications
5
17
0
2
Order By: Relevance
“…Similar to a recently published population-based study in a mainly white population 2 but in contrast to several older studies [7][8][9][10][11][12] that used different stroke classifications and included different ethnical groups, the present study found cardioembolism to be the most common etiology of stroke (25.6%) in our almost exclusively white study population. Cardioembolic stroke particularly dominated in the oldest age group.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to a recently published population-based study in a mainly white population 2 but in contrast to several older studies [7][8][9][10][11][12] that used different stroke classifications and included different ethnical groups, the present study found cardioembolism to be the most common etiology of stroke (25.6%) in our almost exclusively white study population. Cardioembolic stroke particularly dominated in the oldest age group.…”
Section: Discussionsupporting
confidence: 87%
“…In the absence of brain neuroimaging or necropsy examination, a diagnosis of probable ICH was made in the presence of clinical manifestations reflecting increased intracranial pressure such as headache and vomiting, decreased alertness or coma, and gradual progression to death within 24 hours of onset. 11,12 Secondary ICHs were diagnosed in the presence of ruptured aneurysms, arteriovenous malformations, tumors, venous thrombosis, trauma, anticoagulation, or other known causes of ICHs. Patients who could not be categorized as ischemic, hemorrhagic, or due to subarachnoid hemorrhage because of the absence of adequate clinical signs or symptoms, and confirmatory investigations were included among those with ill-defined or unclassified cerebrovascular events (International Classification of Diseases, 9th Revision codes 436 to 437).…”
Section: Definitionsmentioning
confidence: 99%
“…The risk factors were hypertension, cardiac disease, diabetes mellitus, previous TIA, and previous stroke; standard criteria were used to define hypertension, cardiac disease, and diabetes mellitus. 6 The diagnostic tests included computed tomography of the brain (CT), lumbar puncture, invasive cerebral angiography, radionuclide brain scanning, electrocardiography (ECG), and electroencephalography (EEG). As a measure of severity, level of consciousness at admission was scored for all patients as alert, disoriented/lethargic, or stuporous/comatose.…”
mentioning
confidence: 99%